Thematic review series: The Pathogenesis of Atherosclerosis The oxidation hypothesis of atherogenesis: the role of oxidized phospholipids and HDL - Mohamad Navab (Journal of Lipid Research, 2004)
For more than two decades, there has been continuing evidence of lipid oxidation playing a central role in atherogenesis. The oxidation hypothesis of atherogenesis has evolved to focus on specific proinflammatory oxidized phospholipids that result from the oxidation of LDL phospholipids containing arachidonic acid and that are recognized by the innate immune system in animals and humans. These oxidized phospholipids are largely generated by potent oxidants produced by the lipoxygenase and myeloperoxidase pathways. The failure of antioxidant vitamins to influence clinical outcomes may have many explanations, including the inability of vitamin E to prevent the formation of these oxidized phospholipids and other lipid oxidation products of the myeloperoxidase pathway. Preliminary data suggest that the oxidation hypothesis of atherogenesis and the reverse cholesterol transport hypothesis of atherogenesis may have a common biological basis.The levels of specific oxidized lipids in plasma and lipoproteins, the levels of antibodies to these lipids, and the inflammatory/anti-inflammatory properties of HDL may be useful markers of susceptibility to atherogenesis. Apolipoprotein A-I (apoA-I) and apoA-I mimetic peptides may both promote a reduction in oxidized lipids and enhance reverse cholesterol transport and therefore may have therapeutic potential.